Qualitative Analysis on the Factors Affecting Exclusive Breastfeeding among Working Mothers at Community Health Center in Bangkalan, Madura - Tiyas, Dwi Wahyuning; Murti, Bhisma; Indarto, Dono (Journal of Maternal and Child Health, 2016)
Background: Exclusive breast milk is the main food for infants aged 0-6 months. Breast feeding can be extended up to 2 years with complementary food. The prevalence of exclusive breast feeding is targeted to exceed 80%. Study have shown some factors may determine exclusive breastfeeding among working mothers, such as desire to return to work soon after giving birth, distance from home to the workplace, and supporting facilities (e.g. space, freezer) at the workplace. This study aimed to investigate factors affecting exclusive breast feeding among working mother at the workplace.Subjects and Method: This was a qualitative study with phenomenology approach. This study was conducted at the Community Health Center, Bangkalan, Madura. A total of 9 working mothers were purposively selected as informants. The administrators at the workplace were interviewed as another source of information. Some family members were also selected as informants. The data were collected by interview, observation, taking photos, and document review (e.g. maternal and child health book).Results: Exclusive breastfeeding was associated with workplace support for breastfeeding. Adequacy of breastfeeding facility at the workplace was described by mothers as having a place allocated for expressing breast milk and provision of flexible time to express breast milk other than the usual rest time. Most of mothers who were interviewed breastfed their babies for less than three months. Mothers who worked in workplaces that did not provide breastfeeding rooms and refrigerators were more likely to discontinue breastfeeding. Lack of flexible time to express breast milk was also associated with breastfeeding discontinuation. The existence of policies breastfeeding leave, arrangement for light duty after delivery, and flexible working hours, were associated with breastfeeding.Conclusion: Provision of adequate breastfeeding facilities at the workplace, such as a room in which to express breast milk, and a refrigerator, as well as the existence of policy that allows mothers to have flexible time to express breast milk, are important determinants for exclusive breast feeding among employed mothers.Keywords: exclusive breast feeding, working mothers, workplaceÃÂ Correspondence:ÃÂ Dwi Wahyuning Tiyas. Masters Program in Public Health, Sebelas Maret UniversityJournal of Maternal and Child Health (2016), 1(2): 110-118https://doi.org/10.26911/thejmch.2016.01.02.06